PEMENUHAN HAK NARAPIDANA HAMIL DAN MENYUSUI DI LAPAS RAMAH IBU DAN ANAK: Lembaga Pemasyarakatan Perempuan Kelas IIa Pontianak - Parulian Siagian; Safaruddin Harefa; Nungky Dwi Gayatri; Nina Septiana Jasri Akadol; Defria Puspita Sari Hayuningtyas; Muhamad Khoiron Fadhilah (As-Sidanah, 2026)
The correctional system in Indonesia emphasizes a rehabilitative approach that respects human rights, including the right to health for female inmates who are pregnant and breastfeeding. However, the fulfillment of maternal health rights in correctional institutions still faces several challenges, including limited health facilities, shortages of medical personnel, and limited understanding among inmates regarding their health rights. This community service activity aims to improve female inmates’ understanding of basic maternal health rights for pregnant and breastfeeding mothers and to encourage correctional services that are more responsive to the needs of mothers and children. The program applied the Participatory Action Research (PAR) method, which emphasizes inmates' active participation in identifying problems, discussing possible solutions, and reflecting on the outcomes of the activities. The activity was conducted on July 14, 2025, at the Women’s Correctional Institution Class IIA Pontianak, involving 40 female inmates, including four pregnant inmates and three breastfeeding inmates, with support from correctional officers and an academic team from Universitas Tanjungpura. The program included educational sessions, interactive discussions, and participatory reflections on maternal health rights, nutrition during pregnancy and breastfeeding, and procedures for accessing health services inside and outside the correctional institution. The results show increased understanding of maternal health rights and the importance of proper nutrition and accessible health services. Discussions also identified institutional limitations, including maternal health facilities, lactation support, and availability of medical personnel.